Pengaruh Konten Pornografi Terhadap Kesehatan Otak dan Mental dalam Perspektif Islam - Ria Amanda Putri; Aqeela Adhyanie Hernowo (STIKes Ibnu Sina Ajibarang, 2024)
This study discusses the effects of pornographic content on brain and mental health from an Islamic perspective, by reviewing various scientific literature and the opinions of scholars. From a neurological perspective, pornography causes changes in brain structure, especially in areas that regulate self-control and decision-making, which are similar to the effects of addiction to addictive substances. In addition, impaired short-term memory function and decreased ability to focus are also common effects of pornography consumption. From a psychological perspective, continuous exposure to pornography increases the risk of depression, anxiety, and lowers self-esteem and satisfaction in interpersonal relationships. From an Islamic perspective, the majority of scholars consider pornography to be a prohibited behavior (haram) because it contradicts the principles of morality and self-purity. Pornography is seen as damaging a person's morals and spirituality, as well as disrupting the harmony of social relationships, especially in the context of marriage. Although there is a moderate view that acknowledges that the effects of pornography can vary, the majority of Islamic views agree that pornography consumption has more detrimental effects than benefits. Thus, from both a health and Islamic perspective, pornography is considered harmful to mental, emotional, and spiritual well-being, and should be avoided in order to maintain morality and brain health.